ASSESSMENT OF SERUM AND URINE URIC ACID LEVEL IN RELATION WITH ANTHROPOMETRIC INDICES IN OVERWEIGHT AND OBESE UNIVERSITY UNDERGRADUATE STUDENTS - Onwubuya, Emmanuel Ikechukwu; Ukibe, Nkiruka Rose; Kalu, Ofia Anya; Ukibe, Solomon Nwabueze; Osuagwu, Obinwanne Chikamnario (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Elevated uric acid level is related to a variety of adverse metabolic conditions including gout, obesity, and risk factor for cardiovascular diseases. This prospective study designed to assess the serum and urine uric acid level in relation with anthropometric indices in overweight and obese undergraduate students at NAU, Nnewi, Nigeria. Methods: A total of 302 undergraduate students aged between 18 and 40 years were randomly recruited for the present study. They were grouped based on their body mass index (BMI) as overweight, obese, and control participants. 132 participants were males, of which 21 were obese, 34 were overweight while 77 were normal (control) males. 170 participants were females, of which 56 were obese, 62 were overweight while the remaining 52 were normal (control) females. Fasting blood and 24 h urine sample were aseptically collected from all the participants for determination of serum and urine uric acid. Results: The study observed significantly higher serum uric acid level in obese and overweight males than female and control counterparts (p=0.000, respectively). Urine uric acid level was significantly higher in obese males and females than in their overweight and control counterparts (p=0.000). This shows increase production and accumulation of monosodium urate with decreased uric acid excretion which may result in hyperuricemia and hyperuricosuria which may result in gout. Serum and urine uric acid levels were significantly higher among age range (26–32) and (33–40) years compared with those among age range (18–25) (p<0.05) signifying that uric acid level increases with age. Serum and urine uric acid were significantly positively correlated with BMI, waist circumference, and waist hip ratio (p<0.05). Conclusions: High serum uric acid is a prerequisite for gout and also associated with the metabolic syndrome and risk factors for cardiovascular disease. Proper awareness of the implication of hyperuricemia among undergraduate students is necessary.